(untitled) (Revista do Centro de Estudos Portugueses, 2000)
O presente texto tem como objetivo discutir, a partir do ensaio de Silviano Santiago intitulado A cor da pele, parte da obra do poeta mineiro Adão Ventura. The present text has as objective discusses, starting from the analysis of Silviano Santiago entitled The color of the skin, part of the poet’s Adão Ventura work.